Optimizing A1-Level French Reading Skills Through Interactive Learning Using iSpring Suite - Dewi, Evi Rosyani Dewi; Resowijoyo, De Al Farrel; Setyani, Larasati (Franconesia, 2025)
Reading plays a fundamental role in language acquisition, serving as a gateway to vocabulary development, grammatical awareness, and cross-cultural literacy. At the A1 level of the CEFR, learners are expected to understand simple texts related to familiar themes such as personal details, daily routines, and surrounding objects. However, conventional teaching materials often fall short in providing the supportive, engaging, and multisensory experiences that beginners need. The integration of iSpring Suite can address these gaps by offering interactive, scenario-based reading tasks that align with Constructivist Learning Theory, which posits that learners build knowledge through active, meaningful engagement (Piaget, Vygotsky). Additionally, iSpring leverages the principles of Cognitive Load Theory (Sweller), using multimedia formats—text, audio, visuals—to reduce memory strain and enhance comprehension. This aligns with Communicative Language Teaching (CLT), which promotes authentic communication through real-life scenarios and dialogues. Despite its advantages, the use of iSpring should be critically examined. Developing quality modules demands significant time and expertise. Accessibility issues, such as limited internet or device availability, may hinder its reach. Moreover, excessive reliance on digital tools could overlook essential social and cultural aspects of language learning. Nonetheless, when grounded in sound pedagogy and implemented thoughtfully, iSpring Suite offers a dynamic, learner-centered approach to reading instruction. Its adaptability, interactive features, and immediate feedback mechanisms have the potential to significantly improve reading proficiency among A1-level French learners.